2021
DOI: 10.1186/s12936-021-03724-z
|View full text |Cite
|
Sign up to set email alerts
|

Community knowledge, attitudes and practices towards malaria in Ha-Lambani, Limpopo Province, South Africa: a cross-sectional household survey

Abstract: Background Malaria remains a global health concern and is endemic in Limpopo, Mpumalanga and KwaZulu Natal Provinces of South Africa, which aims to eliminate malaria by 2025. Community engagement plays a significant role in improving the acceptability and effectiveness of programmes aimed at reducing malaria transmission. The success of such intervention efforts depends on the knowledge, attitudes and practices (KAP) of the community, and understanding the KAP of community residents may support… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 25 publications
11
5
0
Order By: Relevance
“…Due to the extensive spotlight on malaria among these communities by the national malaria elimination programme, the results of this study showed adequate knowledge, attitude and practice in the prevention and control of malaria, which is consistent with other studies [ 26 30 ]. Similar to the findings of this study, the study by Munajat et al conducted among Indigenous population in Kelantan showed almost half of the participants had adequate knowledge on the causes and symptoms of malaria [ 15 ].…”
Section: Discussionsupporting
confidence: 91%
“…Due to the extensive spotlight on malaria among these communities by the national malaria elimination programme, the results of this study showed adequate knowledge, attitude and practice in the prevention and control of malaria, which is consistent with other studies [ 26 30 ]. Similar to the findings of this study, the study by Munajat et al conducted among Indigenous population in Kelantan showed almost half of the participants had adequate knowledge on the causes and symptoms of malaria [ 15 ].…”
Section: Discussionsupporting
confidence: 91%
“…In this study, female participants were found to be more knowledgeable (69.8%) about malaria than their male counterparts (57.3%), suggesting a need for awareness creation towards malaria for the males. This is supported by study conducted in Ha-Lambani, Limpopo Province, South Africa [ 44 ], which also reported that more female participants had knowledge on malaria transmission and symptoms than males. Similarly, significantly higher proportion of females (57.0%) had good practices towards malaria than males (45.5%) ( P = 0.05).…”
Section: Discussionsupporting
confidence: 52%
“…Most of the respondents correctly identified the 3 most common symptoms of malaria (headache, chills and fever). This coincides with the results of other studies indicating that people in malaria endemic areas are aware of the clinical manifestations of the disease [ 11 , 12 ]. However, incorporating local terminology and knowledge into malaria education and public health promotion may not be effective at changing community knowledge in the shortest possible time.…”
Section: Discussionsupporting
confidence: 91%